Pilosella bulgarica (Asteraceae) a new hybridogenous species from Bulgaria - Szeląg, Zbigniew; Vladimirov, Vladimir (Phytotaxa, 2020)
The newly described Pilosella bulgarica combines the morphological features of P. pavichii and P. rhodopea, and grows in the subalpine habitats in the Kurudere gorge in the Triglav massif, Central Stara Planina Mountains, Bulgaria. It is illustrated with photos of the holotype (kept at SOM) and living plants in the locus classicus.